2013
DOI: 10.1002/lary.24138
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for elective neck dissection with salvage laryngectomy? A decision‐analysis model

Abstract: Based on our decision-analysis model, we do not recommend routine elective neck dissection during salvage total laryngectomy after failure of chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The role of elective neck dissection during STL remains unclear. Although some authors have illustrated improved survival outcomes with elective neck dissection, [20][21][22] others have demonstrated no benefit. 23,24 In our cohort, the rate of occult nodal disease among patients who underwent neck dissection in the absence of preoperative clinically evident nodal burden was 5%.…”
Section: Discussionmentioning
confidence: 99%
“…The role of elective neck dissection during STL remains unclear. Although some authors have illustrated improved survival outcomes with elective neck dissection, [20][21][22] others have demonstrated no benefit. 23,24 In our cohort, the rate of occult nodal disease among patients who underwent neck dissection in the absence of preoperative clinically evident nodal burden was 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the value of elective neck dissection during salvage laryngectomy was examined using a decision‐analysis model . Based on the limited data in the subject, neck dissection was not recommended as obligatory in every salvage laryngectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of a 6 per cent rate of occult nodal disease is consistent with contemporaneous studies analysing the same head and neck subsites as the present investigation, the vast majority of which report a rate between 5 and 20 per cent. 3,10,11,1316 One study reported a higher rate of 28.3 per cent, but suggested that this may be a result of ‘differences in pathological assessment, or the presence of non-viable tumour cells’. 9…”
Section: Discussionmentioning
confidence: 99%
“…One recent study 16 has questioned the sensitivity of occult nodal disease rate as a decision-making tool, and suggested replacing it with risk of regional recurrence when designing decision algorithms for salvage surgery. This was based on lower rates of regional-only recurrence (0–8 per cent) compared with occult metastases (3–18 per cent) in the contemporaneous literature that they considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation